Vascular cognitive impairment and vascular dementia. Issue 5 (May 2018) - Bonnici-Mallia, Anne M.; Barbara, Christopher; Rao, Rahul
Vascular dementia is the second-most-common type of dementia. Vascular cognitive impairment is a term encompassing vascular dementia as well as milder forms of pre-dementia cognitive impairment related to vascular damage that do not meet the criteria for a diagnosis of dementia. Early diagnosis of cerebrovascular disease, including silent infarcts and small vessel disease is difficult, but important, as modification of cardiovascular risk factors is the mainstay of management to decrease further insults and deterioration, and maintain the patient's independence within their family and social unit.